Preparation of Biodegradable Silk Fibroin/Alginate Blend Films for Controlled Release of Antimicrobial Drugs - Yaowalak Srisuwan; Yodthong Baimark (Advances in Materials Science and Engineering)
Silk fibroin (SF)/alginate blend films have been prepared for controlled release of tetracycline hydrochloride, an antimicrobial model drug. The blend films were analysed by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and UV-vis spectroscopy. The functional groups of the SF/alginate blends were monitored from their FTIR spectra. The homogeneity of the blend films was observed from SEM images. The dissolution and film transparency of the blend films depended on the SF/alginate blend ratio. The in vitro drug release profile of the blend films was determined by plotting the cumulative drug release versus time. It was found that the drug release significantly decreased as the SF/alginate blend ratio increased. The results demonstrated that the SF/alginate blend films should be a useful controlled-release delivery system for water-soluble drugs.